High-Frequency and Ultra-High Frequency Ultrasound: Musculoskeletal Imaging up to 70 MHz - Albano, Domenico; Aringhieri, Giacomo; Messina, Carmelo; De Flaviis, Luca; Sconfienza, Luca Maria (Seminars in Musculoskeletal Radiology, 2020)
Musculoskeletal (MSK) ultrasound has well-established advantages, able to investigate very small structures with high resolution and a quick and real-time dynamic evaluation with the possibility of contralateral comparison. Thus ultrasound has kept its own almost exclusive fields of application in daily clinical practice, and it is considered the first-level imaging technique to assess tendons, bursae, and capsuloligamentous structures of small peripheral joints as well as peripheral nerves. Up to now, however, clinical MSK ultrasound imaging could not go beyond the first 1 to 2 cm under the skin, using high-frequency probes up to 18 to 20 MHz with spatial resolution just below millimeters. We present the impressive technical advancements leading to image resolution as low as 30 µm using ultra-high frequency ultrasound (UHFUS) probes up to 70 MHz. High-frequency ultrasound and UHFUS, with frequencies ranging from 22 to 70 MHz, are promising tools to evaluate very superficial structures. In the MSK system, only two articles have assessed its value in limited case series. Future developments may be aimed to better assess ultrastructural changes of very superficial peripheral nerves and other thin structures such as pulleys, retinacula, and tendons.
Keywords: ultrasonography; ultra-high frequency ultrasonography; tendon; cartilage; peripheral nerve